THE SETTLEMENT OF DEFAULT IN SHOPEE PAYLATER ELECTRONIC AGREEMENTS - Nursafitri, Hutami; Nurul Intan Sari D, Siti (Awang Long Law Review, 2021)
Information technology-based lending and borrowing facilities such as Shopee Paylater actually have many conveniences for its users. Shopee Paylater is a form of money lending and borrowing services regulated in Article 1 number (3) of the Financial Services Authority Regulation (Peraturan Otoritas Jasa Keuangan/POJK) No. 77/ POJK.1/2016 concerning Information Technology-Based Lending and Borrowing Services. Although the form of the Shopee Paylater agreement is not written, the Sunservanda Pacta principles contained in Article 1338 paragraph (1) of the Civil Code are still valid. In practice, the Shopee Paylater has quite a lot of problems regarding breach of contract by Shopee Paylater users. Researchers are interested in discussing forms of breach of contract arising from the Shopee Paylater electronic agreement and efforts to resolve disputes that arise. The type of research used in this research is normative juridical research by examining literatures such as law and regulations. This study uses secondary data. The results obtained in the practice of information technology-based lending and borrowing services are two types of breach of contract, namely those who are not doing what they are determined to do and those who do what is promised but once it is overdue. The settlement of the Breach of Contract on the Shopee paylater electronic agreement has been stated in the terms and conditions which are carried out by deliberation to reach a consensus, but if its still has not reach a consensus, it can be resolved by final level settlement through arbitration in Indonesia organized by the National Arbitration Board (Badan Arbitrase Nasional Indonesia/ BANI).